Coated active material, electrode material, and battery

By covering the fluoride solid electrolyte layer on the surface of the active substance of the battery, the total pore volume ratio and the coating structure are controlled, the problem of high battery resistance is solved and the performance and durability of the battery are improved.

CN119301774APending Publication Date: 2025-01-10PANASONIC HOLDINGS CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380044361.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-05-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The resistance of existing batteries is large, which affects their performance and durability, especially in the case of oxidation and decomposition of solid electrolytes.

Method used

The coated active substance is coated with a solid electrolyte layer containing fluoride, and the ratio of the total pore volume to the active substance is controlled between 1.2 and 7.2, and the particle structure and pore distribution of the coating layer are adjusted to promote the material between the materials. A good interface is formed to reduce resistance.

Benefits of technology

It effectively reduces the battery's resistance, improves the battery's charging and discharging efficiency and durability, reduces the increase rate of resistance, and ensures the stable operation of the battery under high output power.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301774A_ABST
    Figure CN119301774A_ABST
Patent Text Reader

Abstract

This coated active material (130) is provided with an active material (110) and a coating layer (111) that contains a first solid electrolyte and coats at least a part of the surface of the active material (110), the first solid electrolyte contains a fluoride, and the ratio of the total pore volume of the coated active material (130) to the total pore volume of the active material (110) is 1.2 or more and less than 7.2. This electrode material (1000) is provided with a coated active material (130) and a second solid electrolyte. A battery (2000) according to the present disclosure is provided with: a positive electrode (201) containing an electrode material (1000); a negative electrode (203); and an electrolyte layer (202) disposed between the positive electrode (201) and the negative electrode (203).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a coated active material, an electrode material, and a battery. Background Art

[0002] Non-Patent Document 1 discloses a battery using a sulfide as a solid electrolyte.

[0003] Prior art literature

[0004] Non-patent literature

[0005] Non-patent document 1: Journal of Power Sources 159 (2006), p193-199. Summary of the invention

[0006] Problems to be solved by the invention

[0007] In the prior art, it is desirable to reduce the resistance of a battery.

[0008] Means used to solve problems

[0009] The present disclosure provides a coated active material, the coated active material comprising:

[0010] Active substances, and

[0011] a coating layer comprising a first solid electrolyte and covering at least a portion of the surface of the active material,

[0012] The first solid electrolyte contains fluoride,

[0013] A ratio of the total pore volume of the coated active material to the total pore volume of the active material is 1.2 or more and less than 7.2.

[0014] Effects of the Invention

[0015] According to the present disclosure, the resistance of the battery can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a cross-sectional view showing a schematic structure of the coated active material according to the first embodiment.

[0017] Figure 2 It is a cross-sectional view showing a schematic structure of a coated active material according to a modified example.

[0018] Figure 3 This is a cross-sectional view showing a schematic structure of an electrode material according to the second embodiment.

[0019] Figure 4 This is a cross-sectional view showing a schematic structure of a battery according to Embodiment 3.

[0020] Figure 5 This is a graph showing the relationship between the DC resistance and the ratio of the total pore volume.

[0021] Figure 6 This is a graph showing the relationship between the increase rate of resistance and the ratio of the total pore volume.

[0022] Figure 7 This is a SEM image of the coated active material of Example 6. DETAILED DESCRIPTION

[0023] (Understanding that forms the basis of the present disclosure)

[0024] For example, when the active material is in contact with the solid electrolyte, the solid electrolyte may be oxidatively decomposed during battery charging. This tendency is more pronounced when the solid electrolyte has poor oxidation resistance, such as sulfide solid electrolytes. In order to solve this problem, the surface of the active material is coated with a coating material with excellent oxidation resistance, such as a halide solid electrolyte.

[0025] Here, the present inventors noticed that even if the composition of the coating material is the same, there are differences in battery characteristics, especially resistance. Furthermore, the present inventors found that there is a correlation between the total pore volume and the battery characteristics, and conceived the present disclosure.

[0026] (Overview of one aspect of the present disclosure)

[0027] The coated active material according to the first aspect of the present disclosure includes:

[0028] Active substances, and

[0029] a coating layer comprising a first solid electrolyte and covering at least a portion of the surface of the active material,

[0030] The first solid electrolyte contains fluoride,

[0031] A ratio of the total pore volume of the coated active material to the total pore volume of the active material is 1.2 or more and less than 7.2.

[0032] According to the present disclosure, the resistance of the battery can be reduced.

[0033] The coated active material according to the second aspect of the present disclosure includes:

[0034] Active substances, and

[0035] a coating layer comprising a first solid electrolyte and covering at least a portion of the surface of the active material,

[0036] The first solid electrolyte contains fluoride,

[0037] The total pore volume of the coated active material is 0.001 cm 3 / g or more and less than 0.014 cm 3 / g,

[0038] The median particle size of the coated active material is 3.5 μm or more and 5.5 μm or less.

[0039] According to the present disclosure, the resistance of the battery can be reduced.

[0040] In the third aspect of the present disclosure, for example, based on the coated active material according to the first or second aspect, the coated layer may have a granular structure including a plurality of particles having a diameter of 500 nm or less. If the coated layer has a fine granular structure, the deformation of the coated layer is promoted during the manufacture of the electrode plate, and thus a good interface can be formed between the coated active material and other materials. As a result, the resistance of the battery can be further reduced.

[0041] In the fourth aspect of the present disclosure, for example, based on the coated active material according to any one of the first to third aspects, the coated layer may have a plurality of pores having a diameter of 50 nm or less. If the coated layer has fine pores, the deformation of the coated layer is promoted during the manufacture of the electrode plate, and thus a good interface can be formed between the coated active material and other materials. As a result, the resistance of the battery can be further reduced.

[0042] In the fifth aspect of the present disclosure, for example, based on the coated active material according to any one of the first to fourth aspects, the mass of the coated layer may be 4.5% or less of the mass of the coated active material. According to this configuration, the resistance of the battery can be further reduced.

[0043] In the sixth aspect of the present disclosure, for example, based on the coated active material according to any one of the first to fifth aspects, the active material may be a positive electrode active material. If the technology of the present disclosure is applied to the positive electrode active material, a solid electrolyte having poor antioxidant properties but high ionic conductivity can be used for the positive electrode.

[0044] In the seventh aspect of the present disclosure, for example, based on the coated active material according to any one of the first to sixth aspects, the first solid electrolyte may be represented by the following compositional formula (2). Here, x satisfies 0 < x ≤ 1.2, n is the weighted average valence of the elements contained in M, M is a metal or a semi-metal, and X contains fluorine or contains fluorine and chlorine. When the halide solid electrolyte represented by the compositional formula (2) is used for the battery, the charge and discharge efficiency of the battery can be improved.

[0045] Li 6-nx M x X6…Formula (2)

[0046] In the eighth aspect of the present disclosure, for example, in the coated active material according to the seventh aspect, M may be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti and Zr. According to this configuration, the ion conductivity of the coating layer can be improved, and the resistance of the battery can be effectively reduced.

[0047] In the ninth aspect of the present disclosure, for example, in the coated active material according to the seventh aspect, M may be at least one selected from the group consisting of Al, Ti and Zr. According to this configuration, the ion conductivity of the coating layer can be improved, and the resistance of the battery can be effectively reduced.

[0048] In the tenth aspect of the present disclosure, for example, in the coated active material according to the seventh aspect, M may be at least one selected from the group consisting of Ti and Al. When M contains Al and / or Ti, the halide solid electrolyte exhibits high ion conductivity.

[0049] In the 11th aspect of the present disclosure, for example, in the coated active material according to any one of the 7th to 10th aspects, the ratio of the amount of Li to the total amount of M can be 1.7 to 4.2. With this configuration, the ion conductivity of the first solid electrolyte can be further improved.

[0050] The electrode material according to the twelfth aspect of the present disclosure includes:

[0051] Any one of the first to eleventh aspects of the invention, and

[0052] Second solid electrolyte.

[0053] The electrode material of the present disclosure is suitable for reducing the resistance of a battery.

[0054] In the 13th aspect of the present disclosure, for example, according to the electrode material of the 12th aspect, the second solid electrolyte may include a sulfide solid electrolyte. When the battery includes a sulfide solid electrolyte as the second solid electrolyte, a high effect can be obtained by applying the technology of the present disclosure.

[0055] A battery according to a fourteenth aspect of the present disclosure includes:

[0056] A positive electrode comprising the electrode material according to the twelfth or thirteenth aspect.

[0057] A battery according to a fifteenth aspect of the present disclosure includes:

[0058] A positive electrode comprising the electrode material of the twelfth or thirteenth aspect,

[0059] Negative electrode, and

[0060] An electrolyte layer is disposed between the positive electrode and the negative electrode.

[0061] According to the present disclosure, it is possible to reduce the resistance of a battery and provide a battery with excellent durability.

[0062] (Implementation Method 1)

[0063] Figure 1 1 is a cross-sectional view showing a schematic structure of the coated active material 130 according to Embodiment 1. The coated active material 130 includes an active material 110 and a coating layer 111. The active material 110 is in the shape of particles, for example. The coating layer 111 covers at least a portion of the surface of the active material 110.

[0064] The coating layer 111 is a layer containing a first solid electrolyte. The coating layer 111 is provided on the surface of the active material 110. The first solid electrolyte contains a fluoride.

[0065] The first solid electrolyte may be a solid electrolyte containing halogen. A solid electrolyte containing halogen is often also referred to as a halide solid electrolyte. The halide solid electrolyte has excellent oxidation resistance. In particular, a halide solid electrolyte containing fluorine (F) has excellent oxidation resistance due to its high electronegativity. Therefore, by coating the active material 110 with the first solid electrolyte, oxidation of other solid electrolytes in contact with the active material 110 can be suppressed. Thus, the resistance of the battery, especially the initial resistance, can be reduced.

[0066] The ratio of the total pore volume of the coated active material 130 to the total pore volume of the active material 110 is, for example, less than 7.2. In this case, the resistance of the battery can be reduced. The increase in resistance of the battery caused by the endurance test can also be suppressed. The ratio of the total pore volume can be less than 3.0.

[0067] The ratio of the total pore volume of the coated active material 130 to the total pore volume of the active material 110 is, for example, 1.2 or more. In this case, the resistance of the battery can be reduced. The increase in the resistance of the battery caused by the endurance test can also be suppressed. The ratio of the total pore volume can be 1.6 or more.

[0068] If the ratio of the total pore volume of the coated active material 130 to the total pore volume of the active material 110 is within the above range, the resistance of the battery can be reduced. A large ratio of the total pore volume means that the particle shape of the material of the coating layer 111 existing on the surface of the active material 110 is maintained, and larger pores are formed. Therefore, in the densification process when the electrode plate is manufactured after the coated active material 130, the solid electrolyte and the auxiliary materials (conductive aid, etc.) are mixed, the coating layer 111 will be deformed and densified in accordance with the shape and configuration of each material, and a good interface between the materials can be formed. As a result, it is possible to suppress the generation of peeling and voids at the interface between the materials, so that the reaction area of ​​the battery can be expanded, and as a result, the resistance of the battery can be reduced.

[0069] A small ratio of the total pore volume indicates that the particles of the coating material forming the coating layer are pressed and fixed on the surface of the active material. Therefore, it can be considered that when the ratio of the total pore volume is too small, the coating layer is difficult to deform with other materials, and it is easy to peel off between materials due to physical rebound after the densification process. In addition, a large ratio of the total pore volume indicates that the bonding between the particles of the coating material is weak, and the particles of the coating material are not fully fitted to the surface of the active material but are simply attached. Therefore, when the ratio of the total pore volume is too large, the coating layer is prone to peeling off in the manufacture of the battery plate, and direct contact between the active material and the solid electrolyte is prone to occur. It can be considered that the resistance of the battery increases as a result.

[0070] For the reasons described above, when the ratio of the total pore volume of the coated active material 130 to the total pore volume of the active material 110 is within the above range, the resistance of the battery can be further reduced.

[0071] Total pore volume (cm 3 / g) can be measured by a fully automatic gas adsorption measurement device. Specifically, the total pore volume can be obtained by using nitrogen as the adsorbed gas type and the amount of adsorbed gas at a relative pressure of 0.99. Since the atomic radius of nitrogen is about 0.4nm, nitrogen will not be adsorbed in closed pores. Therefore, the total pore volume is measured for the volume of pores other than closed pores, which are called open pores.

[0072] In this specification, the total pore volume of the active material 110 refers to the total pore volume of the particle group of the active material 110 . Similarly, the total pore volume of the coated active material 130 refers to the total pore volume of the particle group of the coated active material 130 .

[0073] The total pore volume of the active material 110 can be measured by selectively removing the coating layer 111 from the coated active material 130 using an inorganic solvent or an organic solvent. For example, when the first solid electrolyte included in the coating layer 111 is a halide solid electrolyte, the coating layer 111 can be selectively removed by washing the coated active material 130 with a solvent such as water or ethanol.

[0074] The resistance of the battery increases after a predetermined endurance test. The ratio of the resistance after the endurance test to the resistance before the endurance test (initial resistance) is the resistance increase rate (%).

[0075] The increase in resistance caused by the endurance test can be measured by the following method. After the battery is completed, the charge and discharge process is performed. Then, the battery is charged to an appropriate charging voltage of about 2V to 4V. Then, it is discharged at an appropriate rate of about 2C to 4C. The resistance (initial resistance) is calculated by dividing the difference between the open circuit voltage just before discharge and the voltage at the moment 10 seconds after the start of discharge by the discharge current value. The resistance obtained is the resistance before the endurance test. Then, the battery is placed in a high temperature tank set to 60°C, and 90 cycles of charge and discharge are repeated at 1C. Then, the battery is returned to the constant temperature tank at 25°C, and the resistance is measured as described above. The resistance obtained is the resistance after the endurance test.

[0076] The coating layer 111 can uniformly coat the active material 110 .

[0077] The coating layer 111 may cover only a portion of the surface of the active material 110. Since the particles of the active material 110 are in direct contact with each other via the portion not coated by the coating layer 111, the electron conductivity between the particles of the active material 110 is improved. As a result, the battery can operate at a high output power.

[0078] A portion of the coating layer 111 may have a granular structure comprising a plurality of particles having a diameter of 500 nm or less. Particles having a diameter of 500 nm or less are particles of a halide solid electrolyte serving as a coating material. If the coating layer 111 has a fine granular structure, deformation of the coating layer 111 is promoted during manufacture of the electrode plate, thereby enabling a good interface to be formed between the coated active material 130 and other materials. As a result, the resistance of the battery can be further reduced. When the particles are too large, deformation of the solid electrolyte serving as the coating material is required, so it is difficult to obtain the effects described above. The lower limit of the particle diameter is not particularly limited, and is, for example, 5 nm.

[0079] The granular structure refers to a structure in which a plurality of particles having a diameter of 500 nm or less are strung together and arranged irregularly. The diameter of each of the plurality of particles constituting the granular structure may be 50 nm or less.

[0080] The granular structure including a plurality of particles having a diameter of 500 nm or less can be formed by using particles having a sufficiently small diameter as the coating material and appropriately adjusting the energy applied by a processing device when forming the coating layer 111 .

[0081] The coating layer 111 may have a plurality of pores with a diameter of 50 nm or less. If the coating layer 111 has fine pores, deformation of the coating layer 111 is promoted when manufacturing the electrode plate, so that a good interface can be formed between the coated active material 130 and other materials. As a result, the resistance of the battery can be further reduced. The diameter of each of the plurality of pores may be 5 nm or less. The lower limit of the diameter of the pore is not particularly limited, for example, 0.5 nm.

[0082] Pores having a diameter of 50 nm or less can be formed by using particles having a sufficiently small diameter as the coating material and appropriately adjusting the energy applied by a processing device when forming the coating layer 111 .

[0083] The “plurality of particles having a diameter of 500 nm or less” and the “plurality of pores having a diameter of 50 nm or less” can be determined by observing the surface of the coated active material 130 at a magnification of, for example, 50,000 to 100,000 times using a scanning electron microscope.

[0084] The mass of the coating layer 111 may be 4.5% or less of the mass of the coated active material 130. If the mass of the coating layer 111 is 4.5% or less of the mass of the coated active material 130, the resistance of the battery can be further reduced. The lower limit of the mass of the coating layer 111 is not particularly limited, and is, for example, 0.1% of the mass of the coated active material 130.

[0085] The total pore volume of the coated active material 130 can be 0.001 cm 3 / g or more and less than 0.014cm 3 / g. The median particle size of the coated active material 130 may be 3.5 μm or more and 5.5 μm or less. When the total pore volume and the median particle size of the coated active material 130 fall within such a range, the resistance of the battery can be effectively reduced.

[0086] If the total pore volume and median particle size of the coated active material 130 are within the above range, the resistance of the battery can be reduced. Proper adjustment of the total pore volume and median particle size of the coated active material 130 means that the particle shape of the material of the coating layer 111 present on the surface of the active material 110 is maintained. Therefore, in the densification process when the electrode plate is manufactured after the coated active material 130, the solid electrolyte and the auxiliary materials (conductive aid, etc.) are mixed, the coating layer 111 will be deformed and densified in accordance with the shape and configuration of each material, and a good interface between the materials can be formed. As a result, it is possible to suppress the generation of peeling and voids at the interface between the materials, thereby expanding the reaction area of ​​the battery, and as a result, the resistance of the battery can be reduced.

[0087] The total pore volume of the coated active material being less than the above range indicates that the particles of the coating material forming the coating layer are pressed and fixed on the surface of the active material. Therefore, it can be considered that when the total pore volume of the coated active material is too small, the coating layer is difficult to deform in coordination with other materials, and it is easy to peel off between materials due to physical rebound after the densification process is completed. In addition, the large total pore volume of the coated active material indicates that the bonding between the particles of the coating material is weak, and the particles of the coating material are not fully fitted to the surface of the active material but are simply attached. Therefore, when the total pore volume of the coated active material is too large, the coating layer is prone to peeling off in the manufacture of the battery plate, and direct contact between the active material and the solid electrolyte is prone to occur. It can be considered that the resistance of the battery increases as a result.

[0088] The total pore volume of the coated active material 130 can be 0.0024 cm 3 / g or more and 0.006cm 3 / g or less, and can also be 0.0031cm 3 / g or more and 0.006cm 3 / g or less.

[0089] Next, the active material 110 and the coating layer 111 will be described in detail.

[0090] Active Substance 110

[0091] The active material 110 is, for example, a positive electrode active material. If the technology disclosed in the present invention is applied to the positive electrode active material, a solid electrolyte having poor oxidation resistance but high ion conductivity can be used for the positive electrode. Examples of such solid electrolytes include sulfide solid electrolytes, halide solid electrolytes, and the like.

[0092] The positive electrode active material includes a material having the characteristics of absorbing and releasing metal ions (such as lithium ions). As the positive electrode active material, lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxysulfides, transition metal oxynitrides, etc. can be used. In particular, when lithium-containing transition metal oxides are used as the positive electrode active material, the manufacturing cost of the battery can be reduced and the average discharge voltage can be increased. As lithium-containing transition metal oxides, Li(NiCoAl)O2, Li(NiCoMn)O2, LiCoO2, etc. can be listed.

[0093] The positive electrode active material may include Ni, Co and Al. The positive electrode active material may be lithium nickel cobalt aluminum oxide. For example, the positive electrode active material may be Li(NiCoAl)O2. According to this structure, the energy density and charge and discharge efficiency of the battery can be further improved.

[0094] The active material 110 has a particle shape, for example. The shape of the particles of the active material 110 is not particularly limited. The shape of the particles of the active material 110 may be spherical, ellipsoidal, scaly, or fibrous.

[0095] The median particle size of the active material 110 may be greater than 0.1 μm and less than 100 μm. When the median particle size of the active material 110 is greater than 0.1 μm, the coated active material 130 and other solid electrolytes can form a good dispersion state. As a result, the charge and discharge characteristics of the battery are improved. When the median particle size of the active material 110 is less than 100 μm, the diffusion rate of lithium inside the active material 110 can be fully ensured. Therefore, the battery can operate at a high output power.

[0096] In this specification, the “median diameter” refers to the particle diameter at which the cumulative volume in the volume-based particle size distribution is 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzer.

[0097] 《Coating layer 111》

[0098] The coating layer 111 contains a first solid electrolyte. The first solid electrolyte has ion conductivity. The ion conductivity is typically lithium ion conductivity. The coating layer 111 may contain the first solid electrolyte as a main component, or may contain only the first solid electrolyte. "Main component" refers to the component that contains the most by mass ratio. "Containing only the first solid electrolyte" means that no materials other than the first solid electrolyte are actively added except for inevitable impurities. For example, inevitable impurities include raw materials for making the first solid electrolyte, by-products generated when the first solid electrolyte is produced, etc. The ratio of the mass of inevitable impurities to the overall mass of the first coating layer 111 can be less than 5%, less than 3%, less than 1%, or less than 0.5%.

[0099] The median particle size of the particles of the coating material used to form the coating layer 111 can be 500 nm or less. When the median particle size of the particles of the coating material is 500 nm or less, the particles of the coating material can be uniformly diffused on the surface of the active material 110. Furthermore, mechanical energy is applied to the particles of the active material 110 and the coating material to eliminate the voids contained therein, thereby forming a thin and uniform coating layer 111. The median particle size of the particles of the coating material can be 100 nm or less, or it can be 60 nm or less. The lower limit of the median particle size of the particles of the coating material is not particularly limited, for example, it is 1 nm.

[0100] The particles of the coating material used to form the coating layer 111 may be particles of the first solid electrolyte.

[0101] In this specification, a "particle" may be an aggregate of particles or a particle composed of a single particle. That is, a particle may be a secondary particle or a primary particle.

[0102] The specific surface area of the particles of the coating material for forming the coating layer 111 may be 10 m 2 / g or more, or may be 20 m 2 / g or more, or may be 40 m 2 / g or more. A large specific surface area of the particles of the coating material is related to a large volume of the coating material. When the specific surface area of the particles of the coating material is large, the surface of the active material 110 can be uniformly coated. As a result, a uniform coating layer 111 can be formed. The upper limit of the specific surface area of the particles of the coating material is not particularly limited, for example, it is 100 m 2 / g.

[0103] The first solid electrolyte is a solid electrolyte containing fluorine. The first solid electrolyte may contain Li, M, and X. X contains F and may further contain at least one selected from the group consisting of Cl, Br, and I. M may be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr. The ion conductivity and antioxidant property of this material are excellent. Therefore, the coated active material 130 having the coating layer 111 with the first solid electrolyte can improve the charge-discharge efficiency and thermal stability of the battery.

[0104] When X is F, the antioxidant property of the first solid electrolyte can be further improved.

[0105] The halide solid electrolyte as the first solid electrolyte is represented by the following compositional formula (1), for example. In the compositional formula (1), α, β, and δ are each independently a value greater than 0. X contains fluorine.

[0106] Li α M β X δ … Formula (1)

[0107] Compared with a halide solid electrolyte such as LiI formed only of Li and a halogen element, the halide solid electrolyte represented by the compositional formula (1) has a higher ion conductivity. Therefore, when the halide solid electrolyte having the composition represented by the compositional formula (1) is used for a battery, the charge-discharge efficiency of the battery can be improved.

[0108] The halide solid electrolyte as the first solid electrolyte may be represented by the following compositional formula (2). x satisfies 0 < x ≤ 1.2. n is the weighted average valence of the elements contained in M. M is a metal or a semi-metal. X contains fluorine or contains fluorine and chlorine. When the halide solid electrolyte represented by the compositional formula (2) is used for a battery, the charge-discharge efficiency of the battery can be improved.

[0109] Li 6-nx M x X6…Formula (2)

[0110] M may be at least one selected from the group consisting of Ca, Mg, Al, Y, Ti and Zr. By introducing multivalent ions into the crystal structure containing Li and F, the conduction path of lithium ions can be expanded. According to this structure, the ion conductivity of the coating layer 111 can be improved, and the resistance of the battery can be effectively reduced.

[0111] M may be at least one selected from the group consisting of Al, Ti, and Zr. By adding the above-mentioned elements as trivalent or tetravalent multivalent ions to the crystal structure containing Li and F, the conduction path of lithium ions can be expanded. According to this structure, the ion conductivity of the coating layer 111 can be improved, and the resistance of the battery can be effectively reduced.

[0112] M may be at least one selected from the group consisting of Al and Ti. When M contains Al and / or Ti, the halide solid electrolyte exhibits high ion conductivity.

[0113] M may be at least one selected from the group consisting of Al and Y. That is, for the halide solid electrolyte, the metal element may be at least one selected from the group consisting of Al and Y. M may be Al. When M contains Al and / or Y, the halide solid electrolyte exhibits high ion conductivity.

[0114] In order to further improve the ion conductivity of the first solid electrolyte, the ratio of the amount of Li to the total amount of M in the halide solid electrolyte may be 1.7 to 4.2. According to this configuration, the ion conductivity of the first solid electrolyte can be further improved.

[0115] The halide solid electrolyte may be substantially formed of Li, Ti, Al and X. Here, “the halide solid electrolyte is substantially formed of Li, Ti, Al and X” means that the molar ratio (i.e., molar fraction) of the sum of the amounts of substances of Li, Ti, Al and X relative to the sum of the amounts of substances of all elements constituting the halide solid electrolyte is 90% or more. As an example, the molar ratio (i.e., molar fraction) may be 95% or more. The halide solid electrolyte may be formed only of Li, Ti, Al and X.

[0116] The halide solid electrolyte can be represented by the following composition formula (3).

[0117] Li 6-(4-x)b (Ti 1-x M x ) b F6…Formula (3)

[0118] In compositional formula (3), 0 < x < 1 and 0 < b ≤ 1.5 are satisfied. The halide solid electrolyte having such a composition has high ionic conductivity.

[0119] In order to further improve the ionic conductivity of the halide solid electrolyte, in compositional formula (3), M can be Al.

[0120] In order to further improve the ionic conductivity of the halide solid electrolyte, in compositional formula (3), 0.1 ≤ x ≤ 0.9 can be satisfied.

[0121] In compositional formula (3), 0.1 ≤ x ≤ 0.7 can be satisfied.

[0122] The upper limit value and the lower limit value of the range of x in compositional formula (3) can be defined by any combination selected from the values of 0.1, 0.3, 0.4, 0.5, 0.6, 0.67, 0.7, 0.8, and 0.9.

[0123] In order to improve the ionic conductivity of the halide solid electrolyte, in compositional formula (3), 0.8 ≤ b ≤ 1.2 can be satisfied.

[0124] The upper limit value and the lower limit value of the range of b in compositional formula (3) can be defined by any combination selected from the values of 0.8, 0.9, 0.94, 1.0, 1.06, 1.1, and 1.2.

[0125] The halide solid electrolyte can be crystalline or amorphous.

[0126] The shape of the halide solid electrolyte is not particularly limited. The shape of the halide solid electrolyte is, for example, needle-like, spherical, or ellipsoidal. The shape of the halide solid electrolyte can be granular.

[0127] In the case where the shape of the halide solid electrolyte is, for example, granular (such as spherical), the halide solid electrolyte can have a median particle diameter of 0.01 μm or more and 100 μm or less.

[0128] The thickness of the coating layer 111 is, for example, 1 nm or more and 500 nm or less. If the thickness of the coating layer 111 is adjusted appropriately, the contact between the active material 110 and other solid electrolytes can be sufficiently suppressed. The thickness of the coating layer 111 can be determined by thinning the coated active material 130 into a thin film by means such as ion milling and observing the cross section of the coated active material 130 with a transmission electron microscope. The average value of the thickness measured at any plurality of positions (for example, 5 points) can be regarded as the thickness of the coating layer 111.

[0129] The halide solid electrolyte may be a sulfur-free solid electrolyte. In this case, the generation of sulfur-containing gases such as hydrogen sulfide gas from the solid electrolyte can be avoided. A sulfur-free solid electrolyte refers to a solid electrolyte represented by a composition formula that does not contain sulfur elements. Therefore, a solid electrolyte containing a very small amount of sulfur, such as a solid electrolyte having a sulfur content ratio of 0.1% by mass or less, belongs to a sulfur-free solid electrolyte. The halide solid electrolyte may also contain oxygen as an anion other than the halogen element.

[0130] 《Method for producing halide solid electrolyte》

[0131] The halide solid electrolyte can be produced by the following method.

[0132] A plurality of raw material powders corresponding to the target composition are prepared and mixed. The raw material powder may be a halide. The halide may be a compound formed of a plurality of elements including a halogen element.

[0133] For example, when the target composition is Li 2.7 Ti 0.3 Al 0.7 In the case of F6, LiF, TiF4 and AlF3 are prepared as raw material powders at a molar ratio of about 2.7:0.3:0.7 and mixed. At this time, by appropriately selecting the type of raw material powder, the element type of "M" and "X" in the composition formula (1) can be determined. By adjusting the type of raw material powder, the mixing ratio of the raw material powder and the synthesis process, the values ​​of "α", "β", "γ" and "δ" in the composition formula (1) can be adjusted. In order to offset the composition changes that may occur in the synthesis process, the raw material powders can be mixed at a pre-adjusted molar ratio.

[0134] The raw material powders can be mixed using a mixing device such as a planetary ball mill. The raw material powders are reacted with each other by a mechanochemical grinding method to obtain a reactant. The reactant can be calcined in a vacuum or in an inert atmosphere. Alternatively, the mixture of the raw material powders can be calcined in a vacuum or in an inert atmosphere to obtain a reactant. The calcination is performed, for example, at a temperature of 100° C. to 400° C. for more than 1 hour. In order to suppress composition changes that may occur during calcination, the raw material powders can be calcined in a closed container such as a quartz tube. After these steps, a halide solid electrolyte can be obtained.

[0135] 《Method for producing coated active material 130》

[0136] The coated active material 130 can be produced by the following method.

[0137] The powder of the active material 110 and the powder of the first solid electrolyte are mixed in an appropriate ratio to obtain a mixture. The mixture is subjected to a grinding process to impart mechanical energy to the mixture. The grinding process may be performed using a mixing device such as a ball mill. In order to suppress oxidation of the material, the grinding process may be performed in a dry atmosphere and an inactive atmosphere.

[0138] The coated active material 130 can be manufactured by a dry particle composite method. The treatment based on the dry particle composite method includes applying at least one mechanical energy selected from the group consisting of impact, compression and shear to the active material 110 and the first solid electrolyte. The active material 110 and the first solid electrolyte are mixed in an appropriate ratio.

[0139] The device used in the manufacture of the coated active material 130 is not particularly limited, and may be a device capable of imparting mechanical energy of impact, compression or shear to the mixture of the active material 110 and the first solid electrolyte. As devices capable of imparting mechanical energy, there can be cited processing devices (particle composite devices) such as a ball mill, "MECHANO FUSION" (manufactured by Hosokawa Micron Corporation), "Nobilta" (manufactured by Hosokawa Micron Corporation), and "BALANCE GRAN" (manufactured by FREUND-TURBOCorporation).

[0140] "MECHANO FUSION" is a particle compounding device that uses dry mechanical compounding technology based on applying strong mechanical energy to a variety of different raw material powders. In MECHANO FUSION, mechanical energy such as compression, shearing and friction is applied to the raw material powders placed between a rotating container and a press head. This causes the particles to be compounded.

[0141] "Nobilta" is a particle compounding device that uses dry mechanical compounding technology developed from particle compounding technology to compound nanoparticles. Nobilta produces composite particles by applying mechanical energy such as impact, compression, and shear to various raw material powders.

[0142] The "Nobilta" rotates a rotor at high speed in a horizontal cylindrical mixing container with a predetermined gap between the rotor and the inner wall of the mixing container, and repeatedly forces the raw material powder to pass through the gap. In this way, impact, compression and shear forces act on the mixture, and composite particles of the active material 110 and the first solid electrolyte can be produced.

[0143] The "BALANCE GRAN" stirs the powder in a spiral shape from the outer circumference to the inner circumference, has a chopper to promote convection, and has a stirring scraper that rotates in the opposite direction to the chopper. Through these actions, the mixture can be evenly dispersed to produce composite particles.

[0144] In any device, the thickness of the coating layer 111, the total pore volume of the coated active material 130, etc. can be controlled by adjusting the rotation speed, processing time, dosage, particle size of the material, etc. As the processing time increases, the total pore volume decreases. As the rotation speed of the device increases, the total pore volume decreases.

[0145] It should be noted that the treatment based on the above-mentioned device is not essential. The coated active material 130 can be manufactured by mixing the active material 110 with the first solid electrolyte using a mortar, a mixer, etc. The first solid electrolyte can be deposited on the surface of the active material 110 by various methods such as spraying, spray dry coating, electrodeposition, impregnation, and mechanical mixing using a disperser.

[0146] (Variation Example)

[0147] Figure 2 1 is a cross-sectional view showing a schematic structure of a coated active material 140 of a modified example. The coated active material 140 includes an active material 110 and a coating layer 120. In this modified example, the coating layer 120 includes a first coating layer 111 and a second coating layer 112. The first coating layer 111 is a layer including a first solid electrolyte. The second coating layer 112 is a layer including a base material. The first coating layer 111 is located outside the second coating layer 112. According to this structure, the resistance of the battery can be further reduced.

[0148] The first covering layer 111 is the covering layer 111 described in the first embodiment.

[0149] The second covering layer 112 is located between the first covering layer 111 and the active material 110. In this modification, the second covering layer 112 is in direct contact with the active material 110. The second covering layer 112 may include a material having low electron conductivity, such as an oxide material or an oxide solid electrolyte, as a base material.

[0150] In this modification as well, the ratio of the total pore volume of the coated active material 140 to the total pore volume of the active material 110 may be less than 7.2. In this case, the resistance of the battery can be reduced, and the increase in the resistance of the battery caused by the endurance test can also be suppressed.

[0151] In this modification as well, the ratio of the total pore volume of the coated active material 140 to the total pore volume of the active material 110 may be 1.2 or more. In this case, the resistance of the battery can be reduced, and the increase in the resistance of the battery caused by the endurance test can also be suppressed.

[0152] In this modification, the total pore volume of the coated active material 140 can be 0.001 cm 3 / g or more and less than 0.014m 3 / g. The median particle size of the coated active material 140 may be 3.5 μm or more and 5.5 μm or less. When the total pore volume and the median particle size of the coated active material 140 fall within such a range, the resistance of the battery can be effectively reduced.

[0153] Examples of oxide materials include SiO2, Al2O3, TiO2, B2O3, Nb2O5, WO3, and ZrO2. Examples of oxide solid electrolytes include Li-Nb-O compounds such as LiNbO3, Li-BO compounds such as LiBO2 and Li3BO3, Li-Al-O compounds such as LiAlO2, Li-Si-O compounds such as Li4SiO4, Li2SO4, and Li4Ti5O 12 Li-Ti-O compounds such as Li2ZrO3, Li-Zr-O compounds such as Li2MoO3, Li-VO compounds such as LiV2O5, Li-WO compounds such as Li2WO4, etc. The base material may be one selected from these or a mixture of two or more.

[0154] The base material may be a solid electrolyte having lithium ion conductivity. The base material is typically an oxide solid electrolyte having lithium ion conductivity. The oxide solid electrolyte has high ion conductivity and excellent high potential stability. By using an oxide solid electrolyte as a base material, the charge and discharge efficiency of the battery can be improved.

[0155] The base material may be a material containing Nb. The base material typically contains lithium niobate (LiNbO3). According to this structure, the charge and discharge efficiency of the battery can be improved. For the oxide solid electrolyte as the base material, the material described above can also be used.

[0156] In one example, the ion conductivity of the halide solid electrolyte included in the first covering layer 111 is higher than the ion conductivity of the base material included in the second covering layer 112. According to this configuration, oxidation of other solid electrolytes can be further suppressed without sacrificing ion conductivity.

[0157] The thickness of the first coating layer 111 is, for example, greater than 1 nm and less than 500 nm. The thickness of the second coating layer 112 is, for example, greater than 1 nm and less than 500 nm. If the thickness of the first coating layer 111 and the second coating layer 112 is appropriately adjusted, the contact between the active material 110 and other solid electrolytes can be sufficiently suppressed. The thickness of each layer can be determined by the method described above.

[0158] 《Method for producing coated active material 140》

[0159] The coated active material 140 can be produced by the following method.

[0160] First, the second covering layer 112 is formed on the surface of the active material 110. The method for forming the second covering layer 112 is not particularly limited. Examples of the method for forming the second covering layer 112 include a liquid phase covering method and a gas phase covering method.

[0161] For example, in the liquid phase coating method, a precursor solution of the base material is applied to the surface of the active material 110. In the case of forming the second coating layer 112 containing LiNbO3, the precursor solution can be a mixed solution (sol solution) of a solvent, a lithium alkoxide, and a niobium alkoxide. As lithium alkoxide, lithium ethoxide can be listed. As niobium alkoxide, niobium ethoxide can be listed. The solvent is, for example, an alcohol such as ethanol. The amount of lithium alkoxide and niobium alkoxide is adjusted according to the target composition of the second coating layer 112. Water can be added to the precursor solution as needed. The precursor solution can be acidic or alkaline.

[0162] The method of applying the precursor solution to the surface of the active material 110 is not particularly limited. For example, the precursor solution can be applied to the surface of the active material 110 using a tumble granulation coating device. According to the tumble granulation coating device, the precursor solution can be blown onto the active material 110 while the active material 110 is rolled and flowed, and the precursor solution can be applied to the surface of the active material 110. Thus, a precursor film is formed on the surface of the active material 110. Then, the active material 110 coated with the precursor film is heat-treated. The gelation of the precursor film is promoted by the heat treatment, and the second coating layer 112 is formed.

[0163] Examples of the vapor phase coating method include pulsed laser deposition (PLD), vacuum evaporation, sputtering, thermal chemical vapor deposition (CVD), plasma chemical vapor deposition, etc. For example, in the PLD method, a high-energy pulse laser (e.g., KrF excimer, wavelength: 248 nm) is irradiated on an ion conductive material as a target, and the sublimated ion conductive material is deposited on the surface of the active material 110. When forming the second coating layer 112 of LiNbO3, LiNbO3 sintered to a high density is used as a target.

[0164] However, the method for forming the second covering layer 112 is not limited to the above method, and the second covering layer 112 can be formed by various methods such as spraying, spray dry coating, electrodeposition, dipping, and mechanical mixing using a disperser.

[0165] After the second covering layer 112 is formed, the first covering layer 111 is formed by the method described in Embodiment 1. In this way, the covered active material 140 can be obtained.

[0166] (Implementation Method 2)

[0167] Figure 3 This is a cross-sectional view showing a schematic structure of an electrode material 1000 according to the second embodiment.

[0168] The electrode material 1000 includes the coated active material 130 of the first embodiment and the second solid electrolyte 100. The electrode material 1000 may be a positive electrode material. The coated active material 140 of the modified example may be used instead of the coated active material 130, or the coated active material 140 of the modified example may be used together with the coated active material 130. The electrode material 1000 of this embodiment is suitable for reducing the increase in battery resistance caused by the endurance test.

[0169] The active material 110 covering the active material 130 is separated from the second solid electrolyte 100 by the coating layer 111. The active material 110 does not need to be in direct contact with the second solid electrolyte 100. This is because the coating layer 111 has ion conductivity.

[0170] The second solid electrolyte 100 may include at least one selected from the group consisting of a halide solid electrolyte, a sulfide solid electrolyte, an oxide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte.

[0171] Examples of the halide solid electrolyte include the materials described as the first solid electrolyte in Embodiment 1. That is, the composition of the second solid electrolyte 100 may be the same as or different from that of the first solid electrolyte.

[0172] The oxide solid electrolyte is a solid electrolyte containing oxygen. The oxide solid electrolyte may further contain anions other than sulfur and halogen elements as anions other than oxygen.

[0173] As oxide solid electrolytes, for example, NASICON solid electrolytes represented by LiTi2(PO4)3 and its element substitution products, (LaLi)TiO3-based perovskite solid electrolytes, and Li 14 ZnGe4O 16 , Li4SiO4, LiGeO4 and their element substitution bodies are represented by LISICON type solid electrolytes, such as Li7La3Zr2O 12 Garnet-type solid electrolytes represented by Li3PO4 and its element substitution bodies, Li3PO4 and its N substitution bodies, glass or glass ceramics with Li2SO4, Li2CO3 and other materials added to the basic materials containing Li-BO compounds such as LiBO2 and Li3BO3.

[0174] As a polymer solid electrolyte, for example, a compound of a polymer compound and a lithium salt can be used. The polymer compound can have an ethylene oxide structure. The polymer compound having an ethylene oxide structure can contain a large amount of lithium salt. Therefore, the ion conductivity can be further improved. As lithium salts, LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2F)2, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, etc. can be listed. One lithium salt selected from them can be used alone, or a mixture of two lithium salts selected from them can be used.

[0175] As the complex hydride solid electrolyte, for example, LiBH4-LiI, LiBH4-P2S5, etc. can be used.

[0176] The second solid electrolyte 100 may contain Li and S. In other words, the second solid electrolyte 100 may contain a sulfide solid electrolyte. The sulfide solid electrolyte has high ion conductivity and can improve the charge and discharge efficiency of the battery. On the other hand, the sulfide solid electrolyte sometimes has poor oxidation resistance. In the case where the battery contains a sulfide solid electrolyte as the second solid electrolyte 100, a high effect can be obtained by applying the technology disclosed in the present invention.

[0177] As sulfide solid electrolytes, for example, Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P0.75 S4, Li 10 GeP2S 12 etc. LiX, Li2O, MO can be added to them q , Li p MO q Here, X in "LiX" is at least one selected from the group consisting of F, Cl, Br and I. q ” and “Li p MO q The element M in "MO" is at least one selected from the group consisting of P, Si, Ge, B, Al, Ga, In, Fe and Zn. q ” and “Li p MO q " In this equation, p and q are independent natural numbers.

[0178] The second solid electrolyte 100 may include two or more materials selected from the materials listed as the solid electrolyte. For example, the second solid electrolyte 100 may include a halide solid electrolyte and a sulfide solid electrolyte.

[0179] The second solid electrolyte 100 may have a higher lithium ion conductivity than the first solid electrolyte.

[0180] The second solid electrolyte 100 may contain inevitable impurities such as starting materials, by-products, and decomposition products used when synthesizing the solid electrolyte. The same applies to the first solid electrolyte.

[0181] The shape of the second solid electrolyte 100 is not particularly limited, and may be a needle shape, a sphere shape, an ellipsoidal sphere shape, etc. The shape of the second solid electrolyte 100 may be a particle shape.

[0182] When the second solid electrolyte 100 is in a granular shape (e.g., spherical), the median particle size may be 100 μm or less. When the median particle size is 100 μm or less, the coated active material 130 and the second solid electrolyte 100 may form a good dispersion state in the electrode material 1000. Therefore, the charge and discharge characteristics of the battery are improved. The median particle size of the second solid electrolyte 100 may be 10 μm or less.

[0183] The median particle size of the second solid electrolyte 100 may be smaller than the median particle size of the coated active material 130. With this configuration, the second solid electrolyte 100 and the coated active material 130 can be dispersed in a better state in the electrode material 1000.

[0184] The median particle size of the coated active material 130 may be greater than 0.1 μm and less than 100 μm. When the median particle size of the coated active material 130 is greater than 0.1 μm, the coated active material 130 and the second solid electrolyte 100 may form a good dispersion state in the electrode material 1000. As a result, the charge and discharge characteristics of the battery are improved. When the median particle size of the coated active material 130 is less than 100 μm, the diffusion rate of lithium inside the coated active material 130 may be sufficiently ensured. Therefore, the battery can operate at a high output power.

[0185] The median particle size of the coated active material 130 may be larger than the median particle size of the second solid electrolyte 100. Thus, the coated active material 130 and the second solid electrolyte 100 can be in a well-dispersed state.

[0186] In the electrode material 1000, the second solid electrolyte 100 and the coated active material 130 are as follows. Figure 3 At this time, the coating layer 111 and the second solid electrolyte 100 are in contact with each other.

[0187] The electrode material 1000 may include a plurality of particles of the second solid electrolyte 100 and a plurality of particles of the coated active material 130. That is, the electrode material 1000 may be a mixture of the powder of the coated active material 130 and the powder of the second solid electrolyte 100.

[0188] In the electrode material 1000 , the content of the second solid electrolyte 100 and the content of the coated active material 130 may be the same or different.

[0189] 《Other Materials》

[0190] In the electrode material 1000, for the purpose of improving the adhesion between particles, a binder can be included. The binder is used to improve the adhesion of the material constituting the electrode. As a binder, polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polycarbonate, polyether sulfone, polyether ketone, polyether ether ketone, polyphenylene sulfide, hexafluoropolypropylene, styrene-butadiene rubber, carboxymethyl cellulose, ethyl cellulose, etc. can be listed. In addition, copolymers of more than two monomers selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, butadiene, styrene, pentafluoropropylene, fluoromethyl vinyl ether, acrylate, acrylic acid and hexadiene can also be used. One selected from these may be used alone or two or more may be used in combination.

[0191] Based on the reason of excellent adhesiveness, the binder can be an elastomer. An elastomer is a polymer with rubber elasticity. The elastomer used as a binder can be a thermoplastic elastomer or a thermosetting elastomer. The binder can include a thermoplastic elastomer. As a thermoplastic elastomer, styrene-ethylene-butylene-styrene (SEBS), styrene-ethylene-propylene-styrene (SEPS), styrene-ethylene-ethylene-propylene-styrene (SEEPS), butadiene rubber (BR), isoprene rubber (IR), chloroprene rubber (CR), nitrile rubber (NBR), styrene-butadiene rubber (SBR), styrene-butadiene-styrene (SBS), styrene-isoprene-styrene (SIS), hydrogenated isoprene rubber (HIR), hydrogenated butyl rubber (HIIR), hydrogenated nitrile rubber (HNBR), hydrogenated styrene-butadiene rubber (HSBR), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), etc. can be listed. One selected from them can be used alone, or two or more can be used in combination.

[0192] The electrode material 1000 may contain a conductive additive for the purpose of improving electronic conductivity. As the conductive additive, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black and Ketjen black, conductive fibers such as carbon fibers or metal fibers, carbon fluoride, metal powders such as aluminum, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, conductive polymer compounds such as polyaniline, polypyrrole, and polythiophene, etc. can be used. When a carbon conductive additive is used, low cost can be achieved.

[0193] The conductive auxiliary agent may be contained in the coating layer 111 .

[0194] 《Method for producing electrode material》

[0195] The electrode material 1000 is obtained by mixing the powder of the coated active material 130 with the powder of the second solid electrolyte 100. There is no particular limitation on the method of mixing the coated active material 130 with the second solid electrolyte 100. The coated active material 130 and the second solid electrolyte 100 may be mixed using a mortar or other tool, or may be mixed using a mixing device such as a ball mill.

[0196] (Implementation 3)

[0197] Embodiment 3 will be described below. The description overlapping with Embodiment 1 and Embodiment 2 will be omitted as appropriate.

[0198] Figure 4 2 is a cross-sectional view showing a schematic structure of a battery 2000 according to Embodiment 3. The battery 2000 includes a positive electrode 201, a separator layer 202, and a negative electrode 203. The separator layer 202 is disposed between the positive electrode 201 and the negative electrode 203. The positive electrode 201 includes the electrode material 1000 described in Embodiment 2. According to this structure, an increase in resistance of the battery 2000 due to a durability test can be suppressed, and a battery with excellent durability can be provided.

[0199] The thickness of each of the positive electrode 201 and the negative electrode 203 can be 10 μm or more and 500 μm or less. When the thickness of the positive electrode 201 and the negative electrode 203 is 10 μm or more, sufficient energy density of the battery can be ensured. When the thickness of the positive electrode 201 and the negative electrode 203 is 500 μm or less, the battery 2000 can operate at high output power.

[0200] The separator layer 202 is an electrolyte layer containing an electrolyte material. The separator layer 202 may contain at least one solid electrolyte selected from the group consisting of a sulfide solid electrolyte, an oxide solid electrolyte, a halide solid electrolyte, a polymer solid electrolyte, and a complex hydride solid electrolyte. The details of each solid electrolyte are as described in Embodiments 1 and 2.

[0201] The thickness of the separator layer 202 may be greater than 1 μm and less than 300 μm. When the thickness of the separator layer 202 is greater than 1 μm, the positive electrode 201 and the negative electrode 203 can be more reliably separated. When the thickness of the separator layer 202 is less than 300 μm, the battery 2000 can operate at a high output power.

[0202] The negative electrode 203 includes a material having a property of storing and releasing metal ions (for example, lithium ions) as a negative electrode active material.

[0203] As the negative electrode active material, metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. can be used. The metal material can be a single metal. Alternatively, the metal material can also be an alloy. As metal materials, lithium metal, lithium alloys, etc. can be listed. As carbon materials, natural graphite, coke, graphitized carbon, carbon fiber, spherical carbon, artificial graphite, amorphous carbon, etc. can be listed. From the perspective of capacity density, silicon (Si), tin (Sn), silicon compounds, tin compounds, etc. can be appropriately used.

[0204] The median particle size of the particles of the negative electrode active material may be 0.1 μm or more and 100 μm or less.

[0205] The negative electrode 203 may include other materials such as a solid electrolyte. As the solid electrolyte, the materials described in Embodiment 1 or 2 can be used.

[0206] Example

[0207] Hereinafter, the present disclosure will be described in detail using examples and comparative examples. It should be noted that the present disclosure is not limited to the following examples.

[0208] <Example 1>

[0209] [Production of halide solid electrolyte]

[0210] In an argon atmosphere with a dew point below -60°C, weigh LiF, TiF4 and AlF3 as raw material powders at a molar ratio of LiF:TiF4:AlF3=2.7:0.3:0.7. Put them together with a 0.5 mmφ ball (25 g) into a 45cc pot for a planetary ball mill. Add γ-butyrolactone (GBL) as an organic solvent dropwise into the pot in such a way that the solid content ratio reaches 50% by mass. The solid content ratio is calculated by {(mass of raw material) / (mass of raw material + mass of solvent)}×100. Grind the mixture using a planetary ball mill at 500 rpm for 12 hours. After grinding, separate the balls to obtain a slurry. Use an electric heating mantle to dry the slurry at 200°C for 1 hour under a nitrogen flow. Crush the obtained solid material with a mortar to obtain a powder of a halide solid electrolyte. The halide solid electrolyte has a composition composed of Li 2.7 Ti 0.3 Al 0.7 The composition represented by F6 (hereinafter referred to as "LTAF") In the SEM image, the diameter of each particle of the halide solid electrolyte is in the range of 10 nm to 100 nm.

[0211] [Preparation of coated active material]

[0212] As a positive electrode active material, powder of Li(NiCoAl)O2 (hereinafter referred to as "NCA") is prepared. Next, a coating layer formed of LTAF is formed on the surface of NCA. The coating layer is formed by a stirring treatment using a large-scale high-speed mixer (BG-25L manufactured by FREUND-TURBOCorporation). Specifically, NCA and LTAF are weighed in such a manner as to form a mass ratio of NCA:LTAF=97.3:2.7. Using a high-speed mixer, NCA and LTAF are stirred and mixed at 700 rpm for 1 hour. Then, NCA and LTAF are further stirred and mixed at 1300 rpm for 1 hour. Thus, the coated active material of Example 1 is obtained.

[0213] In Table 1, for example, the expressions "rotation speed 700 rpm, 1300 rpm" and "treatment time 1+1" mean that the treatment is performed at a rotation speed of 1700 rpm for 1 hour and then at a rotation speed of 1300 rpm for 1 hour.

[0214] [Measurement of total pore volume]

[0215] The total pore volume of the coated active material was measured under the following conditions. 3 g of the coated active material was placed in a test tube for measurement, and the test tube was connected to a specific surface area-pore distribution measuring device (BELSORP MINI manufactured by MicrotracBEL Corp.). Then, a nitrogen adsorption / desorption test was performed under the conditions of an adsorption temperature of 77 K and an upper limit of an adsorption relative pressure of 0.99 (P / P0) to obtain an adsorption / desorption isotherm. For the adsorption / desorption isotherm, the analysis software Belmaster7 was used to perform an analysis based on the BJH method (Barrett-Joyner-Halenda method) to calculate the total pore volume.

[0216] The total pore volume of the coated active material in Example 1 is 0.006 cm 3 / g. The total pore volume of NCA was also measured in the same way. The total pore volume of NCA is 0.00197 cm 3 The ratio of the total pore volume of the coated active material to the total pore volume of NCA was 3.0.

[0217] [Measurement of median particle size]

[0218] The median particle size (d50) of the coated active material of Example 1 was measured. The measurement was performed using a laser diffraction / scattering particle size distribution analyzer (LA-960 manufactured by Horiba, Ltd.). The median particle size (d50) of the coated active material of Example 1 was 4.8 μm.

[0219] [Preparation of sulfide solid electrolyte]

[0220] In an argon glove box with a dew point below -60°C, Li2S and P2S5 are weighed in a molar ratio of Li2S:P2S5=75:25. They are crushed and mixed in a mortar to obtain a mixture. Then, the mixture is ground using a planetary ball mill (P-7 model manufactured by Fritsch) at 510 rpm for 10 hours. Thus, a glassy solid electrolyte is obtained. The glassy solid electrolyte is heat treated in an inactive atmosphere at 270°C for 2 hours. Thus, a glass-ceramic-like Li2S-P2S5 as a sulfide solid electrolyte is obtained.

[0221] [Battery production]

[0222] (Production of positive electrode)

[0223] The coated active material and the sulfide solid electrolyte of Example 1 are weighed in such a manner as to form a volume ratio of (coated active material): (sulfide solid electrolyte) = 6:4. They are added to a tetrahydroxynaphthalene solvent together with vapor-grown carbon fiber (VGCF) as a conductive aid and styrene-ethylene-butylene-styrene block copolymer (SEBS) as a binder. The resulting mixture is fully dispersed using an ultrasonic homogenizer to prepare a positive electrode paste. The amount of the conductive aid is 3 parts by mass relative to 100 parts by mass of the coated active material. The amount of the binder is 0.4 parts by mass relative to 100 parts by mass of the coated active material. "VGCF" is a registered trademark of Lisennoco Corporation.

[0224] (Production of negative electrode)

[0225] Lithium titanate and sulfide solid electrolyte as negative electrode active materials are weighed in a volume ratio of (lithium titanate): (sulfide solid electrolyte) = 6.5:3.5. They are added to a tetralin solvent together with vapor-grown carbon fiber (VGCF) as a conductive aid and styrene-ethylene-butylene-styrene block copolymer (SEBS) as a binder. The resulting mixture is fully dispersed using an ultrasonic homogenizer to prepare a negative electrode paste. The amount of the conductive aid is 1 part by mass relative to 100 parts by mass of the negative electrode active material. The amount of the binder is 2 parts by mass relative to 100 parts by mass of the negative electrode active material.

[0226] (Production of all-solid-state batteries)

[0227] The positive electrode paste was applied to an aluminum foil as a positive electrode current collector by a doctor blade method using a coating device to form a coating film. The coating film was dried on a hot plate at 100° C. for 30 minutes. Thus, a positive electrode having a positive electrode current collector and a positive electrode active material layer was obtained.

[0228] Next, the positive electrode is pressed. The electrolyte layer forming paste is applied to the surface of the pressed positive electrode active material layer using a die coater to obtain a stack of the positive electrode and the coating film. The stack is dried on a hot plate at 100°C for 30 minutes. Then, the stack is rolled at a linear pressure of 2 ton / cm. Thus, a positive electrode side stack having a positive electrode collector, a positive electrode active material layer and a solid electrolyte layer is obtained. The electrolyte layer forming paste is prepared by dispersing 0.4 parts by mass of acrylate butadiene rubber as a binder and 100 parts by mass of a sulfide solid electrolyte in a heptane solvent using ultrasound.

[0229] The negative electrode paste was applied on a nickel foil as a negative electrode current collector to form a coating film, and the coating film was dried on a hot plate at 100° C. for 30 minutes. Thus, a negative electrode having a negative electrode current collector and a negative electrode active material layer was obtained.

[0230] Next, the negative electrode is pressed. The paste for forming the electrolyte layer is applied to the surface of the pressed negative electrode active material layer using a die coater to obtain a laminate of the negative electrode and the coating film. The laminate is dried on a hot plate at 100°C for 30 minutes. Then, the laminate is rolled at a linear pressure of 2 ton / cm. Thus, a negative electrode side laminate having a negative electrode collector, a negative electrode active material layer and a solid electrolyte layer is obtained.

[0231] The positive electrode side laminate and the negative electrode side laminate are punched and processed separately to prepare a specified shape. The positive electrode side laminate and the negative electrode side laminate are stacked in a manner that the solid electrolyte layers are in contact with each other. Then, the positive electrode side laminate and the negative electrode side laminate are rolled at 130°C and a line pressure of 2 ton / cm. Thus, a power generation element having a positive electrode, a solid electrolyte layer and a negative electrode in sequence is obtained. The positive terminal and the negative terminal are installed on the obtained power generation element, and a container made of a laminated film is sealed and constrained at a pressure of 5 MPa, thereby obtaining the all-solid-state battery of Example 1.

[0232] [DC resistance measurement]

[0233] The DC resistance of the all-solid-state battery was measured as follows. Constant current charging was performed at a current of 1C. After the cell voltage reached 2.95V, constant voltage charging was performed at 2.95V, and charging was terminated when the charging current reached 0.01C. Then, constant current discharge was performed at a current of 1C, and discharge was terminated when the cell voltage dropped to 1.5V.

[0234] In order to measure the DC resistance, the all-solid-state battery was charged again to 2.2V at a current of C / 3, and then discharged at a current of 4C. The DC resistance (initial resistance) was calculated by dividing the difference between the open circuit voltage just before the 4C discharge and the voltage at the moment when 10 seconds had passed from the start of the discharge by the current value of 4C. The results are shown in Table 1.

[0235] [Durability test]

[0236] The all-solid-state battery was placed in a 60°C thermostat and charged and discharged for 90 cycles at a current of 1C. Then, the all-solid-state battery was returned to the 25°C thermostat and the DC resistance was measured according to the method described above to calculate the DC resistance after the endurance test. The ratio of the DC resistance after the endurance test to the DC resistance before the endurance test was calculated as the resistance increase factor.

[0237] <Example 2>

[0238] The coated active material of Example 2 was prepared in the same manner as in Example 1 except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour, at 1300 rpm for 1 hour, and at 1950 rpm for 1 hour. Then, the total pore volume of the coated active material of Example 2 was measured in the same manner as in Example 1. Using the coated active material of Example 2, an all-solid-state battery was prepared in the same manner as in Example 1, and the DC resistance and the rate of increase in resistance were measured.

[0239] <Example 3>

[0240] The coated active material of Example 3 was prepared in the same manner as in Example 1 except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour, 1300 rpm for 1 hour, and 1950 rpm for 2 hours. Then, the total pore volume of the coated active material of Example 3 was measured in the same manner as in Example 1. Using the coated active material of Example 3, an all-solid-state battery was prepared in the same manner as in Example 1, and the DC resistance and the rate of increase in resistance were measured.

[0241] <Example 4>

[0242] The coated active material of Example 4 was prepared in the same manner as in Example 1 except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour, at 1300 rpm for 1 hour, and at 1900 rpm for 10 minutes. Then, the total pore volume of the coated active material of Example 4 was measured in the same manner as in Example 1. Using the coated active material of Example 4, an all-solid-state battery was prepared in the same manner as in Example 1, and the DC resistance and the rate of increase in resistance were measured.

[0243] <Example 5>

[0244] The coated active material of Example 5 was prepared in the same manner as in Example 1 except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour, 1300 rpm for 1 hour, and 1900 rpm for 1 hour. Then, the total pore volume of the coated active material of Example 5 was measured in the same manner as in Example 1. Using the coated active material of Example 5, an all-solid-state battery was prepared in the same manner as in Example 1, and the DC resistance and the rate of increase in resistance were measured.

[0245] <Example 6>

[0246] [Preparation of coated active material]

[0247] As a positive electrode active material, NCA powder is prepared. Next, a coating layer is formed on the surface of NCA using LTAF having a particle diameter of 10 nm to 100 nm. The coating layer is formed by stirring treatment using a small high-speed mixer (BG-2L manufactured by FREUND-TURBOCorporation). Specifically, NCA and LTAF are weighed in such a manner as to form a mass ratio of NCA:LTAF=97.3:2.7. Using a small high-speed mixer, they are stirred and mixed at 2300 rpm for 1 hour. Then, the rotation speed is changed to 3580 rpm for 1.5 hours of stirring and mixing. Thus, the coated active material of Example 6 is obtained.

[0248] Then, the total pore volume of the coated active material of Example 6 was measured in the same manner as in Example 1. Using the coated active material of Example 6, an all-solid-state battery was prepared in the same manner as in Example 1, and the DC resistance and the resistance increase factor were measured.

[0249] [SEM observation]

[0250] The surface of the coated active material of Example 6 was observed using a scanning electron microscope (Regulus 8220 manufactured by Hitachi High-Tech Corporation, 0.5 kV, 50,000 times). The results are shown in Figure 7 . Figure 7 This is a SEM image of the surface of the coated active material of Example 6. Figure 7In the SEM image, the large bumps and depressions reflect the bumps and depressions of the NCA itself. LTAF particles are attached to the surface of the NCA. The concave parts on the surface of the NCA are buried by the coating layer of LTAF. The coating layer coating the active material has a granular structure P1 containing multiple particles with a diameter of less than 500nm, and the fine particles contained in the granular structure P1 are particles of LTAF as the coating material. In addition, a plurality of pores P2 with a diameter of less than 50nm are formed in the coating layer. The thin film of LTAF exists in a manner that buries the bumps and depressions on the surface of the NCA, and pores P2 are formed in the film. It is speculated that these structures promote the deformation of the coating layer when manufacturing the electrode plate, which helps to form a good interface between the coated active material and other materials.

[0251] <Comparative Example 1>

[0252] The coated active material of Comparative Example 1 was prepared in the same manner as in Example 1 except that the treatment using the high-speed mixer was performed at 700 rpm for 1 hour. Then, the total pore volume of the coated active material of Comparative Example 1 was measured in the same manner as in Example 1. Using the coated active material of Comparative Example 1, an all-solid-state battery was prepared in the same manner as in Example 1, and the DC resistance and the rate of increase in resistance were measured.

[0253] The measurement results of the total pore volume, the measurement results of the DC resistance, and the calculation results of the increase rate of resistance are shown in Table 1. In Table 1, the DC resistance is a relative value when the DC resistance of Comparative Example 1 is regarded as "100". Similarly, the increase rate of resistance is a relative value when the increase rate of resistance of Comparative Example 1 is regarded as "100".

[0254] Figure 5 3 is a graph showing the relationship between the direct current resistance and the ratio of the total pore volume. The horizontal axis shows the ratio of the total pore volume in Table 1. The vertical axis shows the direct current resistance in Table 1. Figure 6 : is a graph showing the relationship between the increase rate of resistance and the ratio of total pore volume. The horizontal axis shows the ratio of total pore volume in Table 1. The vertical axis shows the increase rate of resistance in Table 1. The ratio of total pore volume is the ratio of the total pore volume of the coated active material to the total pore volume of NCA.

[0255] [Table 1]

[0256]

[0257] ※ The DC resistance and resistance increase ratio are relative values ​​when the values ​​of Comparative Example 1 are regarded as 100.

[0258] <Inspection>

[0259] As shown in Table 1 and Figure 5As shown in FIG. 1 , as the ratio of the total pore volume decreases, the DC resistance of the battery decreases. It is speculated that as the treatment time increases, the LTAF particles are firmly attached to the NCA particles, forming an appropriate microstructure, so the adhesion between the coated active material and the sulfide solid electrolyte is improved, and the resistance of the battery is reduced.

[0260] The DC resistance shows a minimum value when the ratio of the total pore volume is 2.4. Examples 2, 3, and 6, which show a ratio of the total pore volume smaller than the ratio of the total pore volume of Example 5, show a greater DC resistance than Example 5. That is, as the ratio of the total pore volume decreases, there is a tendency for the DC resistance to increase. It is speculated that if the ratio of the total pore volume is sufficiently reduced, the surface of the particles coated with the active material becomes sufficiently smooth, and the bonding between other materials such as the sulfide solid electrolyte and the binder and the coated active material is reduced. However, the battery of Example 3, in which the ratio of the total pore volume is 1.2, also shows a sufficiently low DC resistance and a resistance increase rate.

[0261] As shown in Table 1 and Figure 6 As shown, in the area where the ratio of the total pore volume (horizontal axis) is from 7.2 to 1.6, as the ratio of the total pore volume decreases, the increase rate of resistance also decreases. This result shows that the lower the ratio of the total pore volume, the fewer LTAF particles that are not bonded to the active material. In this case, it is possible to avoid the actual reduction in the amount of coating due to the peeling of LTAF particles during the manufacture of the electrode plate. It can be considered that this affects the suppression of the increase in resistance, which is a durability indicator of the battery. On the other hand, it can be considered that in the area where the ratio of the total pore volume is less than 1.6, the reduction in bonding caused by the smoothing of the surface becomes obvious, and the peeling at the interface between the coated active material and other materials is promoted during the durability test. As a result, the increase rate of resistance increases.

[0262] Industrial Applicability

[0263] The technology disclosed herein is useful for, for example, all-solid-state lithium secondary batteries.

Claims

1. A coated active material, The coated active material includes: an active material, and a coating layer that contains a first solid electrolyte and coats at least a part of the surface of the active material, The first solid electrolyte contains a fluoride, The ratio of the total pore volume of the coated active material to the total pore volume of the active material is 1.2 or more and less than 7.

2.

2. A coated active material, The coated active material includes: an active material, and a coating layer that contains a first solid electrolyte and coats at least a part of the surface of the active material, The first solid electrolyte contains a fluoride, The total pore volume of the coated active material is 0.001 cm 3 / g or more and less than 0.014cm 3 / g, The median particle size of the coated active material is 3.5 μm or more and 5.5 μm or less.

3. The coated active material according to claim 1 or 2, wherein the coating layer has a granular structure including a plurality of particles having a diameter of 500 nm or less.

4. The coated active material according to claim 1 or 2, wherein the coating layer has a plurality of pores having a diameter of 50 nm or less.

5. The coated active material according to claim 1 or 2, wherein the mass of the coating layer is 4.5% or less of the mass of the coated active material.

6. The coated active material according to claim 1 or 2, wherein the active material is a positive electrode active material.

7. The coated active material according to claim 1 or 2, wherein the first solid electrolyte is represented by the following compositional formula (2): Li 6-nx M x X6… Formula (2), Here, x satisfies 0 < x ≤ 1.2, n is the weighted average valence of the elements contained in M, M is a metal or a semi-metal, and X contains fluorine or contains fluorine and chlorine.

8. The coated active material according to claim 7, wherein M is at least one selected from the group consisting of Ca, Mg, Al, Y, Ti, and Zr.

9. The coated active material according to claim 7, wherein M is at least one selected from the group consisting of Al, Ti, and Zr.

10. The coated active material according to claim 7, wherein M is at least one selected from the group consisting of Ti and Al.

11. The coated active material according to claim 7, wherein the ratio of the amount of substance of Li to the total amount of substance of M is 1.7 or more and 4.2 or less.

12. An electrode material, which includes: the coated active material according to claim 1 or 2, and a second solid electrolyte.

13. The electrode material according to claim 12, wherein the second solid electrolyte contains a sulfide solid electrolyte.

14. A battery, which includes a positive electrode containing the electrode material according to claim 12.

15. A battery, which includes: a positive electrode containing the electrode material according to claim 12, a negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode.